A method for preparing sodium fluorosilicate using fluorosilicic acid

The fluorosilicate produced by pickling high-purity quartz sand is solved by multiple steps such as flocculation, slow addition of sodium sulfate aqueous glycerol solution and crystal cultivation, and finally drying through fluidized beds, solving the problems of poor uniformity of sodium fluorosilicate particles and low crystallinity, achieving high purity and high crystallinity preparation of sodium fluorosilicate.

CN119774621AInactive Publication Date: 2025-04-08LIANYUNGANG JIANGSHAN QUARTZ PRODUCTS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510091421.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, sodium fluorosilicate has poor particle uniformity and low crystallinity, which affects its application in the fields of glass, enamel, wood anti-corrosion, medicine and water treatment.

Method used

The fluorosilicate produced by pickling the high-purity quartz sand with hydrochloric acid and fluorohydric acid, and then filtration, stirring and concentration, pH adjustment, flocculation treatment, slowly adding sodium sulfate glycerol aqueous solution, cultivating crystals, gradually cooling, slowly stirring and insulated, and finally obtaining sodium fluorosilicate through fluidized bed drying.

Benefits of technology

The particle size distribution of sodium fluorosilicate particles is achieved, with high purity and high crystallinity, and the quality and use effect of the product are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing sodium fluorosilicate using fluorosilicic acid, the steps of which include (1) regulating the mass fraction of fluorosilicic acid to be controlled at 12-14wt% to obtain a fluorosilicic acid mother liquor; (2) adjusting the pH of the fluorosilicic acid mother liquor to 3-4, adding a mixed flocculant, and filtering; (3) stirring and maintaining the temperature at 30-35°C, slowly adding a sodium sulfate glycerol aqueous solution with a mass fraction of 27-30wt%, and after the addition is completed, moving to a crystallization tank; (4) stirring at a speed of 20-30rpm, adding seed crystals, growing crystals at a temperature of 35-40°C, crystallizing completely, gradually cooling to 25-30°C, stirring and keeping warm, suction filtering, washing, and drying to obtain sodium fluorosilicate. The method for preparing sodium fluorosilicate using fluorosilicic acid can make the particle size distribution of sodium fluorosilicate particles uniform, and the purity and crystallinity are high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing sodium fluorosilicate by utilizing fluorosilicic acid, and belongs to the technical field of sodium fluorosilicate preparation. Background Art

[0002] High-purity quartz sand is purified through quartz stone sorting, roasting / water quenching, crushing / screening, magnetic separation, pickling, flotation, drying, cooling and other processes. Among them, pickling is the acidification of quartz stone (silicon dioxide) and hydrochloric acid (hydrogen chloride) and hydrofluoric acid (hydrogen fluoride) soaking in the reactor, and there will be fluorosilicic acid production. Therefore, waste acid containing a large amount of fluorosilicic acid will be produced during the pickling process. If the waste acid containing a large amount of fluorosilicic acid is directly treated as wastewater, it will cause a waste of fluorosilicic acid resources. Sodium fluorosilicate is a kind of fluoride salt, which is widely used in the fields of glass and enamel, wood preservation, medicine, water treatment, etc. Fluorosilicic acid waste acid can be used as a raw material for preparing sodium fluorosilicate, but the produced sodium fluorosilicate has problems such as poor particle uniformity and low crystallinity, which affect the use of subsequent sodium fluorosilicate products. Summary of the invention

[0003] In order to solve at least one problem existing in the above-mentioned prior art, the present invention provides a method for preparing sodium fluorosilicate using fluorosilicic acid, which can make the particle size distribution of sodium fluorosilicate particles uniform, and have high purity and high crystallinity.

[0004] In order to achieve the above object, the present invention adopts the following technical scheme: a method for preparing sodium fluorosilicate using fluorosilicic acid, comprising the following steps:

[0005] (1) washing high-purity quartz sand with hydrochloric acid and hydrofluoric acid, filtering out the generated fluorosilicic acid to remove the high-purity quartz sand, and then stirring and concentrating at a temperature of 45 to 50° C. to control the mass fraction of fluorosilicic acid to 12 to 14 wt %, to obtain a fluorosilicic acid mother solution;

[0006] (2) Then, the pH of the fluorosilicic acid mother liquor is adjusted to 3-4 with sodium hydroxide solution, and a mixed flocculant is added to agglomerate the tiny particles and colloids in the sewage into larger flocs, and the particles and flocs are removed by filtration;

[0007] (3) placing the filtrate in a reaction kettle, stirring at a speed of 100 to 150 rpm, and maintaining the temperature at 30 to 35° C., and then slowly adding a 27 to 30 wt % sodium sulfate glycerol aqueous solution, after the addition is complete, moving to a crystallization tank;

[0008] (4) Stirring at a speed of 20 to 30 rpm, adding seed crystals to the crystallization tank, growing crystals at a temperature of 35 to 40° C., and completing crystallization, then gradually cooling to 25 to 30° C., stirring and keeping warm at a speed of 8 to 12 rpm for 2 to 3 hours, filtering, and washing once with an alkaline glycerol aqueous solution with a pH of 7.5 to 8, then washing 2 to 3 times with neutral water, and finally drying in a fluidized bed. The fluidized bed drying temperature is controlled below 100° C. This temperature range can effectively avoid evaporation and thermal decomposition of fluoride, ensuring the quality and stability of the product. The control of the drying inlet temperature and the exhaust temperature is an important factor affecting the drying effect of sodium fluorosilicate. The inlet temperature should be controlled at 160 to 210° C., and the exhaust temperature should be controlled at 60 to 75° C. to obtain sodium fluorosilicate.

[0009] Preferably, the stirring speed in step (1) is 200-250 rpm.

[0010] Preferably, the concentration of the sodium hydroxide solution in step (2) is 10 to 15 wt %.

[0011] Preferably, the amount of the mixed flocculant added in step (2) is 0.1 to 0.2% of the mass of the fluorosilicic acid mother liquor.

[0012] Preferably, the mixed flocculant in step (2) is prepared by mixing polyaluminium chloride and polyacrylamide in a mass ratio of 2:1.

[0013] Preferably, the rate of slow addition in step (3) is 1.2 to 1.5 L / min.

[0014] Preferably, in step (3), the molar ratio of sodium sulfate to fluorosilicic acid is controlled to be 1.01 to 1.02:1.

[0015] Preferably, the purity of the sodium sulfate in step (3) is high purity.

[0016] Preferably, the sodium sulfate glycerol aqueous solution in step (3) is a mixture of glycerol and water in a volume ratio of 3 to 4:1.

[0017] Preferably, the amount of seed crystals added in step (4) is 0.04 to 0.05% of the mass of the fluorosilicic acid mother liquor.

[0018] Preferably, the seed crystal in step (4) is sodium fluorosilicate, and its purity is high-grade purity.

[0019] Preferably, the rate of gradual cooling in step (4) is 0.2-0.4°C / min.

[0020] Preferably, the alkaline glycerol aqueous solution with a pH of 7.5 to 8 in step (4) is a mixture of glycerol and alkaline aqueous solution in a volume ratio of 3:1, and the amount of the glycerol aqueous solution is 3 to 4% of the fluorosilicic acid mother liquor.

[0021] Preferably, the aqueous alkali solution in step (4) is an aqueous sodium hydroxide solution.

[0022] Preferably, the amount of neutral water used each time in step (4) is 4-5% of the fluorosilicic acid mother liquor.

[0023] Preferably, the temperature of the fluidized bed in step (4) is 70-80°C.

[0024] The invention has the beneficial effects as follows: the method for preparing sodium fluorosilicate of the invention uses fluorosilicic acid as a raw material, and adds it in the form of sodium sulfate glycerol aqueous solution, so that the fluorosilicic acid reacts with sodium sulfate, and grows crystals, so that the particle size distribution of sodium fluorosilicate particles is uniform and the crystallinity is relatively high; in addition, the method for preparing sodium fluorosilicate of the invention further improves the crystallinity and the uniformity of particle size distribution of sodium fluorosilicate particles through stage cooling, slow stirring and heat preservation during the crystallization process; the method for preparing sodium fluorosilicate of the invention uses a mixed flocculant to remove impurities in the early stage, adds sodium sulfate in the form of sodium sulfate glycerol aqueous solution, uses stage cooling, slow stirring and heat preservation during the crystallization process, and uses glycerol alkaline aqueous solution and water for washing after filtration, so that the sodium fluorosilicate particles have higher purity and higher yield. DETAILED DESCRIPTION

[0025] The following is a clear and complete description of the technical solutions in the implementation of the present invention. The described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents, instruments, and components used, they are all conventional products that can be purchased commercially.

[0026] The waste fluorosilicic acid of the present invention is produced by acidification of a reaction kettle soaked with quartz stone, hydrochloric acid and hydrofluoric acid.

[0027] Example 1

[0028] A method for preparing sodium fluorosilicate using fluorosilicic acid comprises the following steps:

[0029] (1) washing high-purity quartz sand with hydrochloric acid and hydrofluoric acid, filtering out the generated fluorosilicic acid to remove the high-purity quartz sand, and then stirring and concentrating at a temperature of 45 to 50° C. and a rotation speed of 200 rpm to control the mass fraction of fluorosilicic acid to 12.1 wt %, to obtain 7.8 kg of fluorosilicic acid mother liquor;

[0030] (2) adjusting the pH of the fluorosilicic acid mother liquor to 3.6 with a 10 wt % sodium hydroxide solution, adding 7.8 g of a mixed flocculant prepared by mixing polyaluminium chloride and polyacrylamide in a mass ratio of 2:1, aerating the wastewater with a Roots blower at 200 rpm to agglomerate the tiny particles and colloids in the wastewater into larger flocs, and filtering to remove the particles and flocs;

[0031] (3) placing the filtrate in a reaction kettle, stirring at a speed of 150 rpm, and maintaining the temperature at 30-35° C., and then slowly adding 3.456 kg of a 27.2 wt % sodium sulfate glycerol aqueous solution at a rate of 1.2 L / min. After the addition is complete, move to a crystallization tank;

[0032] Using sodium sulfate of high purity, dissolving sodium sulfate in a glycerol aqueous solution prepared by mixing glycerol and water in a volume ratio of 4:1 at 30-35° C. to prepare a 27.2 wt % sodium sulfate glycerol aqueous solution;

[0033] (4) stirring at a speed of 30 rpm, adding 3.12 g of high-grade pure sodium fluorosilicate seed crystals to the crystallization tank, growing crystals at a temperature of 40° C., and then gradually cooling to 30° C. at a rate of 0.2-0.4° C. / min, stirring and keeping warm for 3 h at a speed of 12 rpm, filtering, washing once with 0.312 kg of alkaline glycerol aqueous solution of pH 7.7, and then washing three times with neutral water, each time with 0.312 kg of neutral water, and finally drying in a fluidized bed at a temperature of 80° C. to obtain 0.93 kg of sodium fluorosilicate, with a yield of 75.48% and a water content of 0.063%;

[0034] The alkaline glycerol aqueous solution is a mixture of glycerol and an alkaline aqueous solution in a volume ratio of 3:1, and the alkaline aqueous solution is a sodium hydroxide aqueous solution;

[0035] It was determined that the crystallinity of sodium fluorosilicate was 93.2%, the purity was 99.92%, the average particle size was 12.3 μm, and the particle size dispersion was 0.185.

[0036] Example 2

[0037] A method for preparing sodium fluorosilicate using fluorosilicic acid comprises the following steps:

[0038] (1) washing high-purity quartz sand with hydrochloric acid and hydrofluoric acid, filtering out the generated fluorosilicic acid to remove the high-purity quartz sand, and then stirring and concentrating at a temperature of 45 to 50° C. and a rotation speed of 220 rpm to control the mass fraction of fluorosilicic acid to 12.9 wt %, to obtain 7.1 kg of fluorosilicic acid mother liquor;

[0039] (2) adjusting the pH of the fluorosilicic acid mother liquor to 4 with a sodium hydroxide solution having a concentration of 12 wt %, adding 7.8 g of a mixed flocculant prepared by mixing polyaluminium chloride and polyacrylamide in a mass ratio of 2:1, aerating the wastewater with a Roots blower at 200 rpm to agglomerate the tiny particles and colloids in the wastewater into larger flocs, and filtering to remove the particles and flocs;

[0040] (3) placing the filtrate in a reaction kettle, stirring at a speed of 120 rpm, and maintaining the temperature at 30-35° C., and then slowly adding 3.217 kg of a 28.5 wt % sodium sulfate glycerol aqueous solution at a rate of 1.4 L / min. After the addition is complete, move the mixture to a crystallization tank;

[0041] Using sodium sulfate of superior purity, dissolving sodium sulfate in a glycerol aqueous solution prepared by mixing glycerol and water in a volume ratio of 3:1 at 30-35° C. to prepare a 28.5 wt % sodium sulfate glycerol aqueous solution;

[0042] (4) stirring at a speed of 25 rpm, adding 3.20 g of high-grade pure sodium fluorosilicate seed crystals to the crystallization tank, growing crystals at a temperature of 38° C., and then gradually cooling to 28° C. at a rate of 0.2-0.4° C. / min, stirring and keeping warm at a speed of 10 rpm for 2.5 h, filtering, and washing once with 0.213 kg of alkaline glycerol aqueous solution with a pH of 7.8, and then washing twice with neutral water, each time with 0.32 kg of neutral water, and then drying in a fluidized bed at a temperature of 75° C. to obtain 0.92 kg of sodium fluorosilicate, with a yield of 76.94% and a water content of 0.062%;

[0043] The alkaline glycerol aqueous solution is a mixture of glycerol and an alkaline aqueous solution in a volume ratio of 3:1, and the alkaline aqueous solution is a sodium hydroxide aqueous solution;

[0044] It was determined that the crystallinity of sodium fluorosilicate was 93.8%, the purity was 99.91%, the average particle size was 11.9 μm, and the particle size dispersion was 0.183.

[0045] Example 3

[0046] A method for preparing sodium fluorosilicate using fluorosilicic acid comprises the following steps:

[0047] (1) washing high-purity quartz sand with hydrochloric acid and hydrofluoric acid, filtering out the generated fluorosilicic acid to remove the high-purity quartz sand, and then stirring and concentrating at a temperature of 45 to 50° C. and a rotation speed of 200 rpm to control the mass fraction of fluorosilicic acid to 13.8 wt %, to obtain 6.4 kg of fluorosilicic acid mother liquor;

[0048] (2) adjusting the pH of the fluorosilicic acid mother liquor to 3.2 with a 12 wt % sodium hydroxide solution, adding 12.8 g of a mixed flocculant prepared by mixing polyaluminium chloride and polyacrylamide in a mass ratio of 2:1, aerating the wastewater with a Roots blower at 150 rpm to agglomerate the tiny particles and colloids in the wastewater into larger flocs, and filtering to remove the particles and flocs;

[0049] (3) placing the filtrate in a reaction kettle, stirring at a speed of 100 rpm, and maintaining the temperature at 30-35° C., then slowly adding 2.971 kg of a 29.9 wt % sodium sulfate glycerol aqueous solution at a rate of 1.5 L / min. After the addition is complete, move to a crystallization tank;

[0050] Using sodium sulfate of superior purity, dissolving sodium sulfate in a glycerol aqueous solution prepared by mixing glycerol and water in a volume ratio of 3.5:1 at 30-35° C. to prepare a 29.9 wt % sodium sulfate glycerol aqueous solution;

[0051] (4) stirring at a speed of 20 rpm, adding 3.20 g of high-grade pure sodium fluorosilicate seed crystals to the crystallization tank, growing the crystals at a temperature of 35° C., and then gradually cooling to 25° C. at a rate of 0.2-0.4° C. / min, stirring and keeping warm at a speed of 10 rpm for 2.5 h, filtering with suction, washing once with 0.224 kg of an alkaline glycerol aqueous solution of pH 8, and then washing twice with neutral water, each time with 0.32 kg of neutral water, and then drying in a fluidized bed at a temperature of 70° C. to obtain 0.908 kg of sodium fluorosilicate, with a yield of 78.74% and a water content of 0.065%;

[0052] The alkaline glycerol aqueous solution is a mixture of glycerol and an alkaline aqueous solution in a volume ratio of 3:1, and the alkaline aqueous solution is a sodium hydroxide aqueous solution;

[0053] It was determined that the crystallinity of sodium fluorosilicate was 94.1%, the purity was 99.91%, the average particle size was 12.5 μm, and the particle size dispersion was 0.181.

[0054] Example 4

[0055] A method for preparing sodium fluorosilicate using fluorosilicic acid comprises the following steps:

[0056] (1) washing high-purity quartz sand with hydrochloric acid and hydrofluoric acid, filtering out the generated fluorosilicic acid to remove the high-purity quartz sand, and then stirring and concentrating at a temperature of 45 to 50° C. and a rotation speed of 220 rpm to control the mass fraction of fluorosilicic acid to 12.5 wt %, to obtain 7.5 kg of fluorosilicic acid mother liquor;

[0057] (2) adjusting the pH of the fluorosilicic acid mother liquor to 3.5 with a 15 wt % sodium hydroxide solution, adding 9 g of a mixed flocculant prepared by mixing polyaluminium chloride and polyacrylamide in a mass ratio of 2:1, aerating the wastewater with a Roots blower at 150 rpm to agglomerate the tiny particles and colloids in the wastewater into larger flocs, and filtering to remove the particles and flocs;

[0058] (3) placing the filtrate in a reaction kettle, stirring at a speed of 100 rpm, and maintaining the temperature at 30-35° C., and then slowly adding 3.196 kg of a 29.5 wt % sodium sulfate glycerol aqueous solution at a rate of 1.5 L / min. After the addition is complete, move to a crystallization tank;

[0059] Using sodium sulfate of superior purity, dissolving sodium sulfate in a glycerol aqueous solution prepared by mixing glycerol and water in a volume ratio of 3:1 at 30-35° C. to prepare a 29.9 wt % sodium sulfate glycerol aqueous solution;

[0060] (4) stirring at a speed of 20 rpm, adding 3 g of high-grade pure sodium fluorosilicate seed crystals to the crystallization tank, growing crystals at a temperature of 40° C., and then gradually cooling to 25° C. at a rate of 0.2-0.4° C. / min, stirring and keeping warm at a speed of 8 rpm for 2.5 h, filtering, and washing once with 0.3 kg of alkaline glycerol aqueous solution of pH 7.5, and then washing twice with neutral water, each time with 0.375 kg of neutral water, and then drying in a fluidized bed at a temperature of 75° C. to obtain 0.931 kg of sodium fluorosilicate, with a yield of 76.06% and a water content of 0.061%;

[0061] The alkaline glycerol aqueous solution is a mixture of glycerol and an alkaline aqueous solution in a volume ratio of 3:1, and the alkaline aqueous solution is a sodium hydroxide aqueous solution;

[0062] It was determined that the crystallinity of sodium fluorosilicate was 93.5%, the purity was 99.93%, the average particle size was 12.1 μm, and the particle size dispersion was 0.186.

[0063] Comparative Example 1

[0064] A method for preparing sodium fluorosilicate using fluorosilicic acid comprises the following steps:

[0065] (1) washing high-purity quartz sand with hydrochloric acid and hydrofluoric acid, filtering out the generated fluorosilicic acid to remove the high-purity quartz sand, and then stirring and concentrating at a temperature of 45 to 50° C. and a rotation speed of 200 rpm to control the mass fraction of fluorosilicic acid to 12.1 wt %, to obtain 7.6 kg of fluorosilicic acid mother liquor;

[0066] (2) adjusting the pH of the fluorosilicic acid mother liquor to 3.6 with a sodium hydroxide solution having a concentration of 10 wt %, adding 7.6 g of a mixed flocculant prepared by mixing polyaluminium chloride and polyacrylamide in a mass ratio of 2:1, aerating the wastewater with a Roots blower at 200 rpm to agglomerate the tiny particles and colloids in the wastewater into larger flocs, and filtering to remove the particles and flocs;

[0067] (3) placing the filtrate in a reaction kettle, stirring at a speed of 150 rpm, and maintaining the temperature at 30-35° C., and then slowly adding 3.455 kg of a 27.3 wt % sodium sulfate aqueous solution at a rate of 1.2 L / min. After the addition is complete, move to a crystallization tank;

[0068] Using sodium sulfate of high purity, dissolving sodium sulfate in water at 30-35° C. to prepare a 27.3 wt % sodium sulfate aqueous solution;

[0069] (4) stirring at a speed of 30 rpm, adding 3.04 g of high-grade pure sodium fluorosilicate seed crystals to the crystallization tank, growing the crystals at a temperature of 40° C., and then gradually cooling to 30° C. at a rate of 0.2-0.4° C. / min, stirring and keeping warm at a speed of 12 rpm for 3 h, filtering with suction, washing once with 0.304 kg of pH 7.7 aqueous solution, and then washing three times with 0.304 kg of neutral water each time, and finally drying in a fluidized bed at a temperature of 80° C. to obtain 0.74 kg of sodium fluorosilicate, with a yield of 61.64% and a water content of 0.19%;

[0070] It was determined that the crystallinity of sodium fluorosilicate was 88.3%, the purity was 99.39%, the average particle size was 14.3 μm, and the particle size dispersion was 0.358.

[0071] Comparative Example 2

[0072] A method for preparing sodium fluorosilicate using fluorosilicic acid, which is similar to the steps in Example 1, except that:

[0073] Sodium sulfate glycerol aqueous solution, at 30-35° C., sodium sulfate is dissolved in a glycerol aqueous solution prepared by mixing glycerol and water in a volume ratio of 2.5:1 to prepare a 27.2 wt % sodium sulfate glycerol aqueous solution;

[0074] It has been determined that the crystallinity of sodium fluorosilicate is 90.8%, the purity is 99.91%, the average particle size is 11.5 μm, the particle size dispersion is 0.211; and the water content is 0.060%.

[0075] Comparative Example 3

[0076] A method for preparing sodium fluorosilicate using fluorosilicic acid, which is similar to the steps in Example 1, except that:

[0077] Sodium sulfate glycerol aqueous solution, at 30-35° C., sodium sulfate is dissolved in a glycerol aqueous solution prepared by mixing glycerol and water in a volume ratio of 4.5:1 to prepare a 27.2 wt % sodium sulfate glycerol aqueous solution;

[0078] It has been determined that the crystallinity of sodium fluorosilicate is 90.5%, the purity is 99.85%, the average particle size is 13.8 μm, the particle size dispersion is 0.235; and the water content is 0.180%.

[0079] Comparative Example 4

[0080] A method for preparing sodium fluorosilicate using fluorosilicic acid, which is similar to the steps in Example 1, except that:

[0081] Sodium sulfate ethanol aqueous solution, at 30-35°C, sodium sulfate is dissolved in water to prepare a 27.2wt% sulfuric acid aqueous solution, and then ethanol is added, the amount of ethanol used is 3 times the amount of water;

[0082] It was determined that the crystallinity of sodium fluorosilicate was 87.9%, the purity was 99.82%, the average particle size was 14.5 μm, the particle size dispersion was 0.242; and the water content was 0.15%.

[0083] By comparing Example 1 with Comparative Examples 1 to 4, using appropriate amounts of glycerol and water as dissolving agents for sodium sulfate is conducive to the orderly growth of sodium fluorosilicate crystals and improves the crystallinity and particle size dispersity.

[0084] Comparative Example 5

[0085] A method for preparing sodium fluorosilicate using fluorosilicic acid comprises the following steps:

[0086] (1) washing high-purity quartz sand with hydrochloric acid and hydrofluoric acid, filtering out the generated fluorosilicic acid to remove the high-purity quartz sand, and then stirring and concentrating at a temperature of 45 to 50° C. and a rotation speed of 200 rpm to control the mass fraction of fluorosilicic acid to 12.2 wt %, to obtain 7.5 kg of fluorosilicic acid mother liquor;

[0087] (2) adjusting the pH of the fluorosilicic acid mother liquor to 3.7 with a 10 wt % sodium hydroxide solution, stirring at a speed of 150 rpm and maintaining the temperature at 30-35° C., and then slowly adding 3.35 kg of a 27.2 wt % sodium sulfate glycerol aqueous solution at a rate of 1.2 L / min. After the addition is completed, move to a crystallization tank;

[0088] Using sodium sulfate of high purity, dissolving sodium sulfate in a glycerol aqueous solution prepared by mixing glycerol and water in a volume ratio of 4:1 at 30-35° C. to prepare a 27.2 wt % sodium sulfate glycerol aqueous solution;

[0089] (3) stirring at a speed of 30 rpm, adding 3.0 g of high-grade pure sodium fluorosilicate seed crystals to the crystallization tank, growing the crystals at a temperature of 40° C., and then gradually cooling to 30° C. at a rate of 0.2-0.4° C. / min, stirring and keeping warm at a speed of 12 rpm for 3 h, filtering, washing once with 0.3 kg of pH 7.5 water, and then washing three times with 0.3 kg of neutral water each time, and finally drying in a fluidized bed at a temperature of 80° C. to obtain 0.89 kg of sodium fluorosilicate, with a yield of 74.5% and a water content of 0.27%;

[0090] The alkaline glycerol aqueous solution is a mixture of glycerol and an alkaline aqueous solution in a volume ratio of 3:1, and the alkaline aqueous solution is a sodium hydroxide aqueous solution;

[0091] It was determined that the crystallinity of sodium fluorosilicate was 92.1%, the purity was 98.84%, the average particle size was 13.8 μm, and the particle size dispersion was 0.192.

[0092] Compared with Comparative Example 5, Example 1 adjusts the pH of the waste acid and uses a mixed flocculant to remove particles and flocs, which helps to improve the purity of the sodium fluorosilicate product.

[0093] Comparative Example 6

[0094] A method for preparing sodium fluorosilicate using fluorosilicic acid comprises the following steps:

[0095] (1) washing high-purity quartz sand with hydrochloric acid and hydrofluoric acid, filtering out the generated fluorosilicic acid to remove the high-purity quartz sand, and then stirring and concentrating at a temperature of 45 to 50° C. and a rotation speed of 200 rpm to control the mass fraction of fluorosilicic acid to 12 wt %, to obtain 7.7 kg of fluorosilicic acid mother liquor;

[0096] (2) adjusting the pH of the fluorosilicic acid mother liquor to 3.6 with a 10 wt % sodium hydroxide solution, adding 7.87 g of a mixed flocculant prepared by mixing polyaluminium chloride and polyacrylamide in a mass ratio of 2:1, aerating the wastewater with a Roots blower at 200 rpm to agglomerate the tiny particles and colloids in the wastewater into larger flocs, and filtering to remove the particles and flocs;

[0097] (3) placing the filtrate in a reaction kettle, stirring at a speed of 150 rpm, and maintaining the temperature at 30-35° C., and then slowly adding 3.44 kg of a 27.1 wt % sodium sulfate glycerol aqueous solution at a rate of 1.2 L / min. After the addition is complete, move the mixture to a crystallization tank;

[0098] Using sodium sulfate of superior purity, dissolving sodium sulfate in a glycerol aqueous solution prepared by mixing glycerol and water in a volume ratio of 4:1 at 30-35° C. to prepare a 27.1 wt % sodium sulfate glycerol aqueous solution;

[0099] (4) stirring at a speed of 30 rpm, adding 3.08 g of high-grade pure sodium fluorosilicate seed crystals to the crystallization tank, growing the crystals at a temperature of 40° C., completely crystallizing, filtering with suction, washing once with 0.308 kg of an alkaline glycerol aqueous solution of pH 7.7, and then washing three times with 0.308 kg of neutral water each time, and finally drying in a fluidized bed at a temperature of 80° C. to obtain 0.62 kg of sodium fluorosilicate, with a yield of 71.46% and a water content of 0.061%;

[0100] The alkaline glycerol aqueous solution is a mixture of glycerol and an alkaline aqueous solution in a volume ratio of 3:1, and the alkaline aqueous solution is a sodium hydroxide aqueous solution;

[0101] It was determined that the crystallinity of sodium fluorosilicate was 87.2%, the purity was 99.94%, the average particle size was 11.9 μm, and the particle size dispersion was 0.284.

[0102] Comparative Example 7

[0103] A method for preparing sodium fluorosilicate using fluorosilicic acid comprises the following steps:

[0104] (1) washing high-purity quartz sand with hydrochloric acid and hydrofluoric acid, filtering out the generated fluorosilicic acid to remove the high-purity quartz sand, and then stirring and concentrating at a temperature of 45 to 50° C. and a rotation speed of 200 rpm to control the mass fraction of fluorosilicic acid to 12 wt %, to obtain 7.7 kg of fluorosilicic acid mother liquor;

[0105] (2) adjusting the pH of the fluorosilicic acid mother liquor to 3.6 with a 10 wt % sodium hydroxide solution, adding 7.87 g of a mixed flocculant prepared by mixing polyaluminium chloride and polyacrylamide in a mass ratio of 2:1, aerating the wastewater with a Roots blower at 200 rpm to agglomerate the tiny particles and colloids in the wastewater into larger flocs, and filtering to remove the particles and flocs;

[0106] (3) placing the filtrate in a reaction kettle, stirring at a speed of 150 rpm, and maintaining the temperature at 30-35° C., and then slowly adding 3.44 kg of a 27.1 wt % sodium sulfate glycerol aqueous solution at a rate of 1.2 L / min. After the addition is complete, move the mixture to a crystallization tank;

[0107] Using sodium sulfate of superior purity, dissolving sodium sulfate in a glycerol aqueous solution prepared by mixing glycerol and water in a volume ratio of 4:1 at 30-35° C. to prepare a 27.1 wt % sodium sulfate glycerol aqueous solution;

[0108] (4) stirring at a speed of 30 rpm, adding 3.08 g of high-grade pure sodium fluorosilicate seed crystals to the crystallization tank, growing the crystals at a temperature of 40° C., and then stirring and keeping the temperature at a speed of 12 rpm for 3 h, filtering with suction, and washing once with 0.308 kg of alkaline glycerol aqueous solution with a pH of 7.7, and then washing three times with 0.308 kg of neutral water each time, and finally drying in a fluidized bed at a temperature of 80° C. to obtain 0.847 kg of sodium fluorosilicate, with a yield of 70.21% and a water content of 0.060%;

[0109] The alkaline glycerol aqueous solution is a mixture of glycerol and an alkaline aqueous solution in a volume ratio of 3:1, and the alkaline aqueous solution is a sodium hydroxide aqueous solution;

[0110] It was determined that the crystallinity of sodium fluorosilicate was 90.3%, the purity was 99.93%, the average particle size was 12.6 μm, and the particle size dispersion was 0.219.

[0111] By comparing Example 1 with Comparative Examples 6 and 7, after crystallization is completed at 35-40° C., the temperature is gradually lowered, slowly stirred and kept warm, which can improve the crystallinity and particle size distribution uniformity of the sodium fluorosilicate particles.

[0112] Comparative Example 8

[0113] A method for preparing sodium fluorosilicate using fluorosilicic acid comprises the following steps:

[0114] (1) washing high-purity quartz sand with hydrochloric acid and hydrofluoric acid, filtering out the generated fluorosilicic acid to remove the high-purity quartz sand, and then stirring and concentrating at a temperature of 45 to 50° C. and a rotation speed of 200 rpm to control the mass fraction of fluorosilicic acid to 12 wt %, to obtain 7.8 kg of fluorosilicic acid mother liquor;

[0115] (2) adjusting the pH of the fluorosilicic acid mother liquor to 3.6 with a 10 wt % sodium hydroxide solution, adding 7.8 g of a mixed flocculant prepared by mixing polyaluminium chloride and polyacrylamide in a mass ratio of 2:1, aerating the wastewater with a Roots blower at 200 rpm to agglomerate the tiny particles and colloids in the wastewater into larger flocs, and filtering to remove the particles and flocs;

[0116] (3) placing the filtrate in a reaction kettle, stirring at a speed of 150 rpm, and maintaining the temperature at 30-35° C., then quickly adding 3.456 kg of a 27.1 wt % sodium sulfate glycerol aqueous solution, and moving the mixture to a crystallization tank;

[0117] Using sodium sulfate of superior purity, dissolving sodium sulfate in a glycerol aqueous solution prepared by mixing glycerol and water in a volume ratio of 4:1 at 30-35° C. to prepare a 27.1 wt % sodium sulfate glycerol aqueous solution;

[0118] (4) stirring at a speed of 30 rpm, adding 3.12 g of high-grade pure sodium fluorosilicate seed crystals to the crystallization tank, growing crystals at a temperature of 40° C., and then gradually cooling to 30° C. at a rate of 0.2-0.4° C. / min, stirring and keeping warm for 3 h at a speed of 12 rpm, filtering, and washing once with 0.312 kg of alkaline glycerol aqueous solution of pH 7.7, and then washing three times with 0.312 kg of neutral water each time, and then drying in a fluidized bed at a temperature of 80° C. to obtain 0.918 kg of sodium fluorosilicate, with a yield of 75.12% and a water content of 0.063%;

[0119] The alkaline glycerol aqueous solution is a mixture of glycerol and an alkaline aqueous solution in a volume ratio of 3:1, and the alkaline aqueous solution is a sodium hydroxide aqueous solution;

[0120] It was determined that the crystallinity of sodium fluorosilicate was 92.9%, the purity was 99.90%, the average particle size was 24.6 μm, and the particle size dispersion was 0.415.

[0121] By comparing Example 1 with Comparative Example 8, slowly adding the sodium sulfate glycerol aqueous solution can greatly reduce the particle size and particle size dispersibility of the sodium fluorosilicate product, which is helpful for the subsequent use of the product, such as product dissolution.

[0122] In addition, in the present invention, the control of the drying inlet air temperature and the tail gas temperature is an important factor affecting the drying effect of sodium fluorosilicate. The inlet air temperature should be controlled at 160-210°C, and the tail gas temperature should be controlled at 60-75°C.

[0123] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit and essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0124] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing sodium fluorosilicate using fluorosilicic acid, characterized in that: The following steps are involved: (1) washing high-purity quartz sand with hydrochloric acid and hydrofluoric acid, filtering out the generated fluorosilicic acid to remove the high-purity quartz sand, and then stirring and concentrating at a temperature of 45 to 50° C. to control the mass fraction of fluorosilicic acid to 12 to 14 wt %, to obtain a fluorosilicic acid mother solution; (2) adjusting the pH of the fluorosilicic acid mother liquor to 3-4 with sodium hydroxide solution, adding a mixed flocculant, and filtering; (3) placing the filtrate in a reaction kettle, stirring at a speed of 100 to 150 rpm, and maintaining the temperature at 30 to 35° C., and then slowly adding a 27 to 30 wt % sodium sulfate glycerol aqueous solution, after the addition is complete, moving to a crystallization tank; (4) Stirring at a speed of 20 to 30 rpm, adding seed crystals to the crystallization tank, growing crystals at a temperature of 35 to 40° C., and then gradually cooling to 25 to 30° C., stirring and keeping warm at a speed of 8 to 12 rpm for 2 to 3 hours, filtering, and washing once with an alkaline glycerol aqueous solution with a pH of 7.5 to 8, then washing 2 to 3 times with neutral water, and finally drying on a fluidized bed to obtain sodium fluorosilicate.

2. A method for preparing sodium fluorosilicate using fluorosilicic acid according to claim 1, characterized in that: In step (3), the molar ratio of sodium sulfate to fluorosilicic acid is controlled to be 1.01-1.02:

1.

3. A method for preparing sodium fluorosilicate using fluorosilicic acid according to claim 1, characterized in that: The rate of slow addition in step (3) is 1.2 to 1.5 L / min.

4. A method for preparing sodium fluorosilicate using fluorosilicic acid according to claim 1, characterized in that: The sodium sulfate glycerol aqueous solution in step (3) is a mixture of glycerol and water in a volume ratio of 3 to 4:1; the purity of the sodium sulfate is high-grade purity.

5. A method for preparing sodium fluorosilicate using fluorosilicic acid according to claim 1, characterized in that: The amount of seed crystals added in step (4) is 0.04-0.05% of the mass of the fluorosilicic acid mother liquor; the seed crystals are sodium fluorosilicate, and the purity of the sodium fluorosilicate is high-grade purity.

6. A method for preparing sodium fluorosilicate using fluorosilicic acid according to claim 1, characterized in that: The rate of gradual cooling in step (4) is 0.2-0.4°C / min.

7. A method for preparing sodium fluorosilicate using fluorosilicic acid according to claim 1, characterized in that: The alkaline glycerol aqueous solution with a pH of 7.5 to 8 in step (4) is a mixture of glycerol and an alkaline aqueous solution in a volume ratio of 3:1; the alkaline aqueous solution is a sodium hydroxide aqueous solution.

8. The method for preparing sodium fluorosilicate using fluorosilicic acid according to claim 1, characterized in that: The temperature of the fluidized bed in step (4) is 70-80°C.

9. A method for preparing sodium fluorosilicate using fluorosilicic acid according to claim 1, characterized in that: The amount of the mixed flocculant added in step (2) is 0.1 to 0.2% of the mass of the fluorosilicic acid mother liquor.

10. A method for preparing sodium fluorosilicate using fluorosilicic acid according to claim 1 or 9, characterized in that: The mixed flocculant in step (2) is prepared by mixing polyaluminium chloride and polyacrylamide in a mass ratio of 2:1.